Perancangan Sistem Informasi Pencarian Apotek Terdekat Berbasis Web dengan Fitur Ketersediaan Obat di Kota Pekanbaru - Marian Tonis; Abdul Zaky; Wulan Patricia; Muhammad Firdaus; Wiwik Suryandartiwi (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Pekanbaru City comprises 15 districts with 373 pharmacies distributed relatively evenly across urban areas, reflecting substantial public demand for pharmaceutical services. However, residents face challenges in locating nearby pharmacies and accessing detailed information including addresses, operating hours, contact numbers, and specific medicine availability. This research developed a websitebased pharmacy location system to address these limitations and provide efficient access to pharmacy information. The study employed quantitative methods and development research design, utilizing direct observation and documentation for data collection from pharmacies throughout Pekanbaru. The resulting prototype web-based system was developed using PHP, HTML, CSS, JavaScript, and MySQL database within the Laragon server environment. The platform demonstrates cross-platform compatibility, functioning effectively on both computer and mobile browsers. Testing confirmed the system's operational reliability and accurate pharmacy location display. The research demonstrates that this web-based solution significantly enhances public access to pharmaceutical information. For sustained effectiveness, regular data updates by the Pekanbaru City Health Office are recommended to maintain information validity and relevance. This system represents a practical solution to improve healthcare accessibility while establishing a framework for efficient pharmacy information management in urban settings.